Pengaruh Gaya Kepemimpinan terhadap Kinerja Tenaga Kesehatan Di Puskesmas Oesapa Kupang Tahun 2023 - Kornelia Saiman; Rina Waty Sirait; Tadeus A.L Regaletha (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Leadership style is a way or pattern of behavior applied by a leader to influence his subordinates to want to carry out the tasks that have been given. Based on an initial survey of researchers at the Oesapa Health Center, leaders rarely supervise the tasks carried out by health workers. The purpose of this study is to determine the influence of leadership style on the performance of health workers. The type of research used is quantitative research. Participants in this study were health workers at Puskemas Oesapa Kupang as many as 60 people, with the sample technique used was non-probability sampling. The data analysis used was chi square analysis and simple linear regression. The results showed that there was an influence of authoritarian leadership style on the performance of health workers at Puskesmas Oesapa Kupang seen from the linear regression equation Y = 2.606 - 0.305X and the significance value was 0.005 < 0.05. There is an influence of democratic leadership style on the performance of health workers at Puskesmas Oesapa Kupang seen from the linear regression equation Y = -1.241 + 1.121X and significance value = 0.007 < 0.05. And there is no influence of free control leadership style on the performance of health workers at the Oesapa Kupang Health Center with a significance value of 0.278 > 0.05. For the Oesapa Health Center, it is recommended that a democratic leadership style be further improved so that the performance of health workers at the Oesapa Health Center increases.